2018
DOI: 10.1097/qai.0000000000001855
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality Among Hospitalized Patients With Lower Respiratory Tract Infections in a High HIV Burden Setting

Abstract: Introduction Lower respiratory tract infections (LRTIs) are a leading cause of mortality in sub-Saharan Africa. Triaging identifies patients at high-risk of death but laboratory tests proposed for use in severity-of-illness scores are not readily available, limiting their clinical use. Our objective was to determine whether baseline characteristics in hospitalized participants with LRTI predicted increased risk of death. Methods This was a secondary analysis from the MIND-IHOP cohort of adults hospitalized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Five studies assessed hypoxemia among specific populations, ranging from those with cor pulmonale to sepsis to Ebola Virus Disease. The heterogeneity in patient populations makes it difficult to discern the overall need in various settings, but prevalence ranged from 11%-89% [ 35 , 37 , 40 , 45 , 46 ]. Several of these studies demonstrated high mortality among those with hypoxemia and an additional two studies focused specifically on hypoxemia as a risk factor for mortality [ 36 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies assessed hypoxemia among specific populations, ranging from those with cor pulmonale to sepsis to Ebola Virus Disease. The heterogeneity in patient populations makes it difficult to discern the overall need in various settings, but prevalence ranged from 11%-89% [ 35 , 37 , 40 , 45 , 46 ]. Several of these studies demonstrated high mortality among those with hypoxemia and an additional two studies focused specifically on hypoxemia as a risk factor for mortality [ 36 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several of these studies demonstrated high mortality among those with hypoxemia and an additional two studies focused specifically on hypoxemia as a risk factor for mortality [ 36 , 42 ]. For example, among hospitalized patients who presented with lower respiratory tract infection and cough at Mulago Hospital in Uganda, 10.6% had an oxygen saturation of <90%, and hypoxemia was associated with both in-hospital and two-month mortality [ 46 ]. Among patients with Ebola Virus Disease in West Africa, 18 of 41 (44%) patients required and received supplemental oxygen via concentrators, and 16 of 18 (89%) died [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because heart rate might be more easily available in LMIC settings than temperature, we also created an alternate clinical score where heart rate replaced temperature (see Additional file 6 , table showing alternate clinical score). In this alternate score, we used heart rate cut-offs of > 120 versus ≤ 120 beats/minute, which were informed by both prior published literature [ 22 , 27 ] and observed inflection points in the association between heart rate and risk of death (see Additional file 5 , figure of association between heart rate and risk of death).…”
Section: Resultsmentioning
confidence: 99%
“…To do so, 5 variables known to be associated with pneumonia severity were selected for adjustment; these were age, heart rate, respiratory rate, oxygen saturation, and whether or not a participant was, by self-report, bedbound. [23,24] Initially, to determine whether differences in biomarker levels were independent of pneumonia severity, we fit a multiple linear regression model for each biomarker as a continuous outcome in which HIV status (infected or uninfected) was the predictor of interest, and co-variates were age, heart rate, respiratory rate, oxygen saturation, and bedbound status. However, regression diagnostics suggested that for several biomarkers, model residuals were not normally distributed and that variance differed substantially between the HIV-infected and HIV-uninfected subgroups.…”
Section: Methodsmentioning
confidence: 99%